HOW TO IMPROVE LISTENING SKILLS FOR ESL STUDENTS - Jollibekova.M; Abdiganiyeva.N (Scholar Express Journals, 2021)
In this article, we will teach ESL students how to understand English speech by ear, how to choose and listen to a podcast appropriate to the topic and level of English, the usefulness of listening lessons, how to learn English correctly from audio materials, what podcasts are, detailed information about the term ESL is given
Keywords: ESL; category; representative; education; vocabulary; listening